The effect of online learning on burnout conditions of students in Medical Faculty, Udayana University - I Nyoman Gede Narendra Yanakusuma; I Gde Haryo Ganesha; Cokorda Agung Wahyu Purnamasidhi (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2021)
Background: Learning in the network (online) is learning by using the internet to access material and interact with teachers and students presented through electronic devices, making it easier to access information anytime, anywhere. Implementing online learning can provide stressful conditions for students, resulting in burnout conditions. Aim: To determine the effect of online learning on the burnout condition of medical faculty students. Methods: This study was an observational study with a cross-sectional study design. The total sample was 325 respondents, and the sampling method used a consecutive sampling technique. Result: The results showed that burnout ratings obtained from 325 subjects received low burnout as many as 118 people (36.3%), moderate burnout as many as 197 people (60.6%), and severe burnout as many as ten people (3.1%). Conclusion: Burnout can occur during the implementation of online learning. There is a sense of saturation, fatigue, and limitations in doing practicum or lab skills so that the lectures that are run will not be optimal.